Peran Guru dalam Menanamkan Nilai-nilai Profil Pelajar Pancasila - Saripatul Aini; Willy Akmansyah Lubis (An-Nuha, 2023)
This study aims to record, analyze, and reflect on the actual contribution of teachers in instilling the values of the Pancasila Student Profile at the elementary school level, specifically at SDN 086 Dalan Lidang, Mandailing Natal. The research is motivated by the gap between national curriculum policies and the practical understanding of teachers, as well as the moral challenges faced by the Alpha generation in the digital era. This study employs a descriptive qualitative approach, with data collection through interviews, observations, questionnaires, and documentation. Data analysis was conducted systematically through data reduction, data display, and conclusion drawing. The results demonstrate that teachers play a crucial role as role models, facilitators, mentors, school culture drivers, and evaluators in internalizing the six dimensions of the Pancasila Student Profile. The findings indicate that students show a strong understanding of the "Faith and Piety" and "Mutual Cooperation" dimensions through daily behavioral habits. However, in the dimensions of "Critical Reasoning" and "Independence," students still require further stimulation due to a persistent dependence on teacher instructions. This study concludes that the success of character education is highly dependent on the commitment and pedagogical awareness of teachers as the primary agents of change in the school environment.